2005
DOI: 10.1007/s10541-005-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Different Glycoprotein IIb-IIIa Ligands to Support Platelet Aggregation Induced by Activating Antibody CRC54

Abstract: The ability of different ligands of glycoprotein (GP) IIb-IIIa (alphaIIb/beta3-integrin) to support platelet aggregation stimulated by activating anti-GP IIb-IIIa monoclonal antibody (monoAB) CRC54 has been investigated. Antibody CRC54 stimulated aggregation of washed platelets not only in the presence of fibrinogen, the main GP IIb-IIIa ligand, but also in the presence of von Willebrand factor (vWF). Unlike these ligands, fibronectin failed to support CRC54-induced aggregation. Fibrinogen and vWF dependent pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The platelet membrane in which GP IIb/IIIa exists as a complex is very important in platelet plug formation after vascular injury (Wang et al, 2006). This complex acts as a receptor for fibrinogen, fibronectin, von Willebrand factor and vitronectin, and its binding of these adhesive proteins mediates platelet aggregation, adhesion and spreading (Naimushin and Mazurov, 2005;Wijeyewickrema et al, 2005). Flow cytometric analysis showed that indole-3-carbinol inhibited the population of FITC fibrinogen bound GP IIb/IIIa in a concentration-dependent manner, suggesting indole-3-carbinol may disrupt the fibrinogen binding to GP IIb/IIIa receptor on platelet surface, suggesting that the inhibitory effect of indole-3-carbinol on platelet aggregation may be mediated by blockage of fibrinogen binding to GP IIb/IIIa receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet membrane in which GP IIb/IIIa exists as a complex is very important in platelet plug formation after vascular injury (Wang et al, 2006). This complex acts as a receptor for fibrinogen, fibronectin, von Willebrand factor and vitronectin, and its binding of these adhesive proteins mediates platelet aggregation, adhesion and spreading (Naimushin and Mazurov, 2005;Wijeyewickrema et al, 2005). Flow cytometric analysis showed that indole-3-carbinol inhibited the population of FITC fibrinogen bound GP IIb/IIIa in a concentration-dependent manner, suggesting indole-3-carbinol may disrupt the fibrinogen binding to GP IIb/IIIa receptor on platelet surface, suggesting that the inhibitory effect of indole-3-carbinol on platelet aggregation may be mediated by blockage of fibrinogen binding to GP IIb/IIIa receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation is investigated using an aggregometer which works on the principle that the transmission of light increases as platelets aggregate [ 46 , 47 ]. Another glycoprotein, activated integrin α IIb β 3, commonly known as gpIIb/IIIa on platelets, is responsible for platelet aggregation by cross-linking platelets with fibrinogen [ 48 ]. Defective gpIIb/IIIa on platelets results in inadequate aggregation, and this condition is called Glanzmann's thrombasthenia [ 49 ].…”
Section: Abnormalities In the Primary Hemostatic Plug Formationmentioning
confidence: 99%
“…Other studies revealed that platelet aggregation induced by MCF-7 cells is mediated in part through an ADPdependent mechanism and that these cells express platelet immunorelated glycoproteins GPIb, GPIIb/IIIa, GPIb/IX, and the integrin αv subunit on their surface [157]. Tumorinduced platelet aggregation is also regulated by plasma proteins, e.g., von Willebrand factor or fibrinogen [158,159]. Studies from Yokota et al [148] provided new insight into thrombin-mediated TF-dependent metastasis based on a hyperthrombotic mouse model with thrombomodulin deficiency (TM Pro mice).…”
Section: Platelet Activation and Aggregationmentioning
confidence: 99%